Membangun Generasi Sehat Melalui Edukasi Parenting untuk Pencegahan Stunting di Dusun Masangan - Dhohirrobbi, Achmad; Camelia Cahyani, Verisa; Wutsqa, Urwatul; Azzam, M. Abdullah; Anjani, Khofifah Tri; Afiroh, Siti; Dharma, Kusuma Sanata; Nugraha, Much. Azhar Fanza; Pusposari, Luthfiya Fathi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Stunting remains a major health challenge in Indonesia, particularly in lower-middle-income regions. The primary cause of stunting is chronic malnutrition during the first 1,000 days of life, exacerbated by poor hygiene and limited access to healthcare facilities. According to the 2022 Indonesian Nutritional Status Survey (SSGI), the national stunting prevalence is 21.6%, with East Java at 19.2%. If left unaddressed, stunting can negatively impact physical and cognitive development, as well as the overall quality of human resources in the future. As a preventive effort, the